Children with Disabilities Attending Montessori Programs in the United States - Long, Toby; Westerman, Clare; Ferranti, Nadia (Journal of Montessori Research, 2022)
Early childhood education plays a critical role in establishing positive social-emotional behaviors and promoting the development of skills needed to succeed in elementary school. Although inclusion of children with disabilities (CWD) in early childhood classrooms is increasing throughout the world, numerous social, logistical, and political factors continue to present challenges to full inclusion. The Montessori educational approach, established at the beginning of the 20th century and now applied widely throughout Europe and the United States, may present a highly suitable learning context for CWD, particularly given its historical basis in efforts to meet the needs of underprivileged and cognitively delayed children. On a theoretical level, the inclusion of CWD should be an accepted practice for Montessori programs yet reports of the number and characteristics of CWD attending Montessori programs are scarce. This paper reports upon the findings of a survey of U.S. Montessori early childhood programs’ current enrollment of CWD. The survey indicated that CWD represent 3.75% of the infant and toddler (0–3 years) population and 8.49% of the preschool/early childhood (3–6 years) population at responding institutions. Additionally, although school directors indicate that their teachers generally feel confident and competent including CWD in their classrooms, they expressed a need for ongoing professional development and additional support from special education experts to further empower the inclusion of CWD in all aspects of Montessori education.